Segmental myocardial velocities in dilated cardiomyopathy with and without left bundle branch block. Issue 1 (14th September 2012) - Foell, Daniela; Jung, Bernd A.; Germann, Elfriede; Staehle, Felix; Bode, Christoph; Hennig, Juergen; Markl, Michael
Abstract Purpose: To quantify three‐directional left ventricular (LV) myocardial velocities and intraventricular synchrony in dilated cardiomyopathy (DCM) with and without left bundle branch block (LBBB) using MR tissue phase mapping (TPM). Materials and Methods: Regional velocities were assessed by TPM (spatial/temporal resolution = 1.3 × 1.3 mm2 × 8 mm/14 ms) in DCM patients with (n = 12) and without LBBB (n = 7) compared with age‐matched volunteers (n = 20). For the evaluation the AHA 16‐segment and an extended LV visualization model was used. Results: Radial velocities in DCM patients were reduced in 75% (systole) and in 94% (diastole) (P = 0.0001 – P = 0.0360), long‐axis velocities in 31% (systole) and in 75% (diastole) of the 16 segments compared with controls (P = 0.0001 – P = 0.0310). LBBB resulted in inferolaterally delayed diastolic long‐axis velocities (P = 0.0012 – P = 0.0464) and shortened TTP for septal systolic radial velocities (P = 0.0002). Intra‐ventricular radial systolic TTP differed up to 150 ms between segments in patients with LBBB (89 ms without LBBB, 34 ms in volunteers) reflecting an increased dyssynchrony. LV twist was altered in all patients with reduced and delayed systolic and diastolic peak velocities. Conclusion: TPM identified previously not described alterations of the spatial distribution and timing of all myocardial velocities in patients with DCM and LBBB. This may help to optimize therapy management in future. J. Magn. Reson. Imaging 2013;37:119–126. © 2012 Wiley Periodicals, Inc.